Relationship between entrepreneurial leadership and school effectiveness among secondary schools - Lope Pihie, Zaidatol Akmaliah; Dahiru, Abbas Sani; Basri, Ramli; Hassan, Siti Aishah (Human Resource Management Academic Research Society, 2018)
There is a general consensus among stakeholders in education that a strong positive educational leadership is a determining factor of school effectiveness. However, many questions were raised as regards to the applicability of entrepreneurial leadership in the context of education. The main purpose of this study is to determine the relationship between entrepreneurial leadership and school effectiveness, and also to identify the dimension of entrepreneurial leadership that contributes more to school effectiveness. The research adopted a survey design and a total sample of 358 secondary school teachers in Zamfara State, Nigeria were selected through simple random sampling from a total population of 4996 as a sample for the study, using Cochran’s sample size determination formula. Data were collected through survey method and were analyzed using both descriptive and inferential (Pearson correlation and multiple regression) statistical analyses. The findings of the study indicated the existence of significant and strong relationship between entrepreneurial leadership practice and school effectiveness (p < 0.05), also accelerator behavior appeared to be the highest predictor of school effectiveness among secondary schools in Zamfara State (β= .335, t = 6.265, p< .01). This implies that entrepreneurial leadership dimension (accelerator behavior) facilitates school effectiveness of secondary school leaders in the study area and efforts should be made towards increasing its level through motivating the teachers.